2022
DOI: 10.5195/jmla.2022.1249
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based biomedical research in Sub-Saharan Africa: how library and information science professionals contribute to systematic reviews and meta-analyses

Abstract: Objective: This study investigated the contributions of library and information science (LIS) professionals to systematic reviews and meta-analyses with authors from Sub-Saharan Africa. It also investigated how the first author’s address and type of collaboration affected the involvement of LIS professionals in systematic reviews and meta-analyses. Methods: Bibliographic data of systematic reviews with author(s) from the forty-six Sub-Saharan African countries was retrieved from MEDLINE. Content and bibliometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Library professionals must adapt to these changes and harness emerging technologies to remain relevant in the digital era. (1,2) Emerging technologies encompass a broad spectrum of innovations that are in the early stages of development and adoption. They include fields such as artificial intelligence (AI), blockchain, quantum computing, biotechnology, augmented and virtual reality (AR/VR), and the Internet of Things (IoT).…”
Section: Understanding Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Library professionals must adapt to these changes and harness emerging technologies to remain relevant in the digital era. (1,2) Emerging technologies encompass a broad spectrum of innovations that are in the early stages of development and adoption. They include fields such as artificial intelligence (AI), blockchain, quantum computing, biotechnology, augmented and virtual reality (AR/VR), and the Internet of Things (IoT).…”
Section: Understanding Emerging Technologiesmentioning
confidence: 99%
“…Another issue is understanding the risks associated with online activities and ensuring safe information practices is crucial in today's digital environment. (2,16) Therefore, librarians need to be well-versed in cybersecurity and privacy issues to protect patrons' data and digital assets.…”
Section: Leveraging Digital Literacy For Self-sufficiencymentioning
confidence: 99%
“…A number of studies indicate that, compared to other parts of the world, African health sciences research has had little scientific impact [ 1 , 2 ]. This is mostly because there are few African journals included in the international citation databases [ 1 , 3 , 4 ], which reduces the visibility of the continent’s health science research. Several studies have reported an increase in scientific impact following indexing of journals in international and regional citation databases as it increases visibility [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%